2021
DOI: 10.1007/s00425-021-03688-z
|View full text |Cite
|
Sign up to set email alerts
|

Localised expression of OsIAA29 suggests a key role for auxin in regulating development of the dorsal aleurone of early rice grains

Abstract: Main ConclusionNon-canonical AUX/IAA protein, OsIAA29, and ZmMPR-1 homologues, OsMRPLs, are part of an auxin-related signalling cascade operating in the dorsal aleurone during early rice grain development.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Aux/IAA is the initial response gene of growth hormone, which is the hub of the growth hormone signaling process [ 33 ]. When growth hormone is at low concentration, Aux/IAA is synthesized in large quantities and the activity of growth hormone response factor (AUXIN RESPONSE FACTOR, ARF) is inhibited; when growth hormone is at higher concentration, the expression of Aux/IAA is degraded by ubiquitination and ARF is activated, and the activated ARF regulates downstream genes controlling the growth hormone signaling pathway [ 34 ]. The results of this study showed that the expression of Aux/IAA was up-regulated after enzymatic degradation compared with fresh young leaves, which indicated that the enzymatic digestion of the cells of young sugarcane leaves significantly affected the expression of Aux/IAA, which might have a certain effect on the response of protoplasts to regulate the growth hormone signaling process during heterozygous cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Aux/IAA is the initial response gene of growth hormone, which is the hub of the growth hormone signaling process [ 33 ]. When growth hormone is at low concentration, Aux/IAA is synthesized in large quantities and the activity of growth hormone response factor (AUXIN RESPONSE FACTOR, ARF) is inhibited; when growth hormone is at higher concentration, the expression of Aux/IAA is degraded by ubiquitination and ARF is activated, and the activated ARF regulates downstream genes controlling the growth hormone signaling pathway [ 34 ]. The results of this study showed that the expression of Aux/IAA was up-regulated after enzymatic degradation compared with fresh young leaves, which indicated that the enzymatic digestion of the cells of young sugarcane leaves significantly affected the expression of Aux/IAA, which might have a certain effect on the response of protoplasts to regulate the growth hormone signaling process during heterozygous cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…An aleurone-specific NF-Y family member, OsNF-YB1, binds to promotors of genes encoding OsSUT1, OsSUT3 and OsSUT4, as well as the auxin biosynthetic gene, OsYUC11. The latter gene product contributes to the transcriptional network controlling auxin levels regulating endosperm differentiation (Bai et al, 2016;Basunia et al, 2021;Xu et al, 2021) and enhancing SUT activities (Fig. 6d; Darussalam et al, 1998;Basunia & Nonhebel, 2019).…”
Section: Regulation Of Sucrose Efflux From Maternal Tissuesmentioning
confidence: 99%
“…Additionally, maize is widely used in agriculture, animal husbandry and industry, for items such as food, animal feed and biofuel production ( Shiferaw et al, 2011 ). Therefore, maize has great economic value, and research on the molecular mechanism of maize growth and development will help producers better guide its daily production ( Basunia et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%